The casual relationship between financial development and macroeconomic growth - Gupta, Karan (2010)
The following paper aims to examine the existence and direction of the causality between financial development and nominal GDP by incorporating time series analysis for 4 emerging Asian economies. The results obtained provide evidence that financial development and macroeconomic growth are mutually causal, supporting the existing literature. However, there is also some support for the view that economic growth leads to financial development but it is not as significant as the existence of the bidirectional causality. Additionally, the findings of the study are harmonious with the view of the World Bank that the above relationship cannot be generalised across various nations as each has a country-specific economic policy.